The Effect of E-Service Quality of MyTelkomsel Application on Customer Satisfaction in Bahu Village, Manado - Mamesah, Sharon Jenifer; Tampi, Johny R. E; Mukuan, Danny D. S (Productivity, 2024)
The purpose of this research is to determine the influence of the MyTelkomsel Application E-Service Quality on Customer Satisfaction. This research uses quantitative research methods. The research population was 100 users of the MyTelkomsel application in Bahu District, Manado, using a purposive sampling technique. The statistical tests used in this research are the validity test, reliability test, simple correlation coefficient test, simple regression analysis test, partial test (t-test), and coefficient of determination test using IBM SPSS Statistics Version 29. Based on the results of statistical tests, it is known that the E-Service Quality variable has a positive and significant influence on the Customer Satisfaction variable with a calculated t value for the E-Service Quality variable of 9.265 with a significance of 0.001. From these results it is known that the calculated t value of 9.265 is greater than the t table value of 1.984, and the significance value of E-Service Quality is 0.001 smaller than the significance (0.05).